Internalisasi Pendidikan Karakter Melalui Keteladanan Ali Bin Abi Thalib Pada Mata Pelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah - Pip Sumardi (GHAITSA : Islamic Education Journal, 2020)
The purpose of this study was to determine: (1) lesson plan on the application of character education through the exemplary values of Ali bin Abi Talib in learning the history of Islamic culture; (2) the implementation of learning on the application of character education through the exemplary values of Ali bin Abi Talib in learning the history of Islamic culture; (3) evaluation of learning on the application of character education through the exemplary values of Ali bin Abi Talib in learning the history of Islamic culture; (4) constraints and solutions to the application of character education through the exemplary values of Ali bin Abi Thalib in learning the history of Islamic culture to students of MIN 2 Bengkulu City. This study uses a qualitative descriptive method which is carried out by emphasizing the process of implementing integrated character education in the learning of Islamic cultural history in the material of Ali bin Abi Thalib. Data collection used observation, interview, and document analysis techniques. Data was collected through resource persons, learning activities, and learning documents. The data validity techniques used were informant review and triangulation, namely method triangulation and data triangulation. The results showed that: (1) lesson planning is contained in the 2013 curriculum-based lesson plan; (2) Ali bin Abi Talib's exemplary values are conveyed to students in the implementation of learning with the Contextual Teaching and Learning (CTL) and Direct Instruction (DI) methods which include the values of intelligence, humility, courage, responsibility, generosity, justice and equality, simplicity, compassion, wisdom, patience, and leadership; (3) learning evaluation is classified according to Bloom's Taxonomy which includes cognitive, affective, and psychomotor domains; (4) learning constraints arise from component factors consisting of students, teachers, and learning resources, as well as technical factors which include lesson time, supervision, and facilities. Islamic Cultural History teachers overcome obstacles with personal approaches, assignments, variations in learning resources, adjusting learning models, and complementing teaching tools.